Hepatitis B core particles with His tags - Tan, Wen Siang; Yap, Wei Boon; Tey, Beng Ti (2009)
Accordingly, the present invention provides a recombinant fusion protein which includes at least one His tags and hepatitis B virus (HBV)core antigen. Further , the present invention also provides a method in producing a recombinant fusion protein which includes at least one His tags and hepatitis B virus (HBV) core antigen, the steps include (a) culturing expression host which contains expression vector of the recombinant fusion protein in a medium that allows growth of the expression host, (b) allowing the recombinant fusion protein to be expressed in the expression host, (c) harvesting the expression host from step (b)from the medium, (d) disrupting the expression host harvested from step (c) in a liquid medium for ultrasonication and (e) purifying the recombinant fusion protein of hepatitis B virus core antigen from the liquid medium. Also provided is a method for purifying a recombinant fusion protein which includes a His tag and hepatitis B virus (HBV) core antigen, the steps include (a)loading unclarified lysate of expression host expressing and containing the recombinant fusionprotein into nickle (II)-charged adsorbent, (b) fractioning the recombinant fusion protein using immobilized metal affinity chromatography and (c)collecting the fractionated recombinant fusion protein obtained from step (c) for determined concentration of the hepatitis B virus (HBV) core antigen. There is also provided a pharmaceutical composition comprising a therapetically effective amount of recombinant fusion protein which includes at least on His tag and hepatitis B virus (HBV) core antigen. Also provided is a vaccine comprising a prophylactic effective amount of a recombinant fusion protein which includes a His tag and hepatitis B virus (HBV) core antigen.